The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.3389/fimmu.2023.1159291
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide from aerial part of Chuanminshen violaceum alleviates oxidative stress and inflammatory response in aging mice through modulating intestinal microbiota

Abstract: Aging is a biological process of progressive deterioration of physiological functions, which poses a serious threat to individual health and a heavy burden on public health systems. As population aging continues, research into anti-aging drugs that prolong life and improve health is of particular importance. In this study, the polysaccharide from stems and leaves of Chuanminshen violaceum was obtained with water extraction and alcohol precipitation, and then separated and purified with DEAE anion exchange chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“… 14 , 36 This heightened oxidative stress is implicated in intensifying inflammation and fostering protein modifications, subsequently leading to the generation of reactive oxygen species and promoting lymphatic infiltration, a phenomenon that aligns with our observed results. 8 , 37 Our findings reveal that both IF and SCD Probiotics effectively mitigated lymphatic infiltration in aged rats, indicating their inherent anti‐inflammatory attributes. 38 , 39 Moreover, our study detected an increase in mast cell densities and up regulated TNF‐α and COX‐2 expression in aged rats, elements that contribute to oxidative stress and inflammation.…”
Section: Discussionmentioning
confidence: 64%
“… 14 , 36 This heightened oxidative stress is implicated in intensifying inflammation and fostering protein modifications, subsequently leading to the generation of reactive oxygen species and promoting lymphatic infiltration, a phenomenon that aligns with our observed results. 8 , 37 Our findings reveal that both IF and SCD Probiotics effectively mitigated lymphatic infiltration in aged rats, indicating their inherent anti‐inflammatory attributes. 38 , 39 Moreover, our study detected an increase in mast cell densities and up regulated TNF‐α and COX‐2 expression in aged rats, elements that contribute to oxidative stress and inflammation.…”
Section: Discussionmentioning
confidence: 64%
“…This phenomenon further propels protein modifications and cultivates environments conducive to lymphatic infiltration, a correlation that our results affirm. 31 , 32 Our study showed that the administration of young plasma to aged rats resulted in a decline in lymphatic infiltration density, 28 , 33 shedding light on its anti‐inflammatory potential. We further investigated changes in mast cell densities in the ileum and colon and the expression levels of inflammatory mediators such as TNF‐α and COX‐2.…”
Section: Discussionmentioning
confidence: 68%
“…The accumulation of this information is important for determining the course of a more precise investigation. However, key concerns, such as the ways of interaction between the microbiome and OS, are not well addressed in many articles [ 36 , 61 , 96 , 97 ]. Although the aims of various types of research are finding correlations between the objects of study and changes in several systems in the organism, the authors quite rarely draw attention to the chemical characteristics or pharmacodynamics of the compound.…”
Section: Discussionmentioning
confidence: 99%
“…Another point that remains unclear is causation. Many compounds, including food supplements, could modulate oxidative balance and bacterial community [ 36 , 51 , 54 , 63 , 64 , 74 , 77 , 93 , 95 , 97 ]; however, these changes might be parallel processes or have a cause–effect relationship. The cause–effect relationships might be in two different directions and with different strengths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation